A graphene-based non-volatile memory - Loisel, Loïc (2018)
We report on the development and characterization of a simple two-terminal non-volatile graphene switch. After an initial electroforming step during which Joule heating leads to the formation of a nano-gap impeding the current flow, the devices can be switched reversibly between two well-separated resistance states. To do so, either voltage sweeps or pulses can be used, with the condition that VSET < VRESET , where SET is the process decreasing the resistance and RESET the process increasing the resistance. We achieve reversible switching on more than 100 cycles with resistance ratio values of 104. This approach of graphene memory is competitive as compared to other graphene approaches such as redox of graphene oxide, or electro-mechanical switches with suspended graphene. We suggest a switching model based on a planar electro-mechanical switch, whereby electrostatic, elastic and friction forces are competing to switch devices ON and OFF, and the stability in the ON state is achieved by the formation of covalent bonds between the two stretched sides of the graphene, hence bridging the nano-gap. Developing a planar electro-mechanical switch enables to obtain the advantages of electro-mechanical switches while avoiding most of their drawbacks.